2014
DOI: 10.1128/mbio.00765-13
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Receptor Antagonists Are Anti-Cryptococcal Agents That Directly Bind EF Hand Proteins and Synergize with Fluconazole In Vivo

Abstract: Cryptococcosis is an infectious disease of global significance for which new therapies are needed. Repurposing previously developed drugs for new indications can expedite the translation of new therapies from bench to beside. Here, we characterized the anti-cryptococcal activity and antifungal mechanism of estrogen receptor antagonists related to the breast cancer drugs tamoxifen and toremifene. Tamoxifen and toremifene are fungicidal and synergize with fluconazole and amphotericin B in vitro. In a mouse model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
133
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(139 citation statements)
references
References 46 publications
(97 reference statements)
6
133
0
Order By: Relevance
“…In view of the inhibitory activity of toremifene against the fungus C. neoformans and the Ebola virus reported previously (17,28), our data further highlight the broad-spectrum antibiofilm activity of toremifene.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…In view of the inhibitory activity of toremifene against the fungus C. neoformans and the Ebola virus reported previously (17,28), our data further highlight the broad-spectrum antibiofilm activity of toremifene.…”
supporting
confidence: 79%
“…We already showed that the antibiofilm activity of toremifene against C. albicans is partly mediated by membrane permeabilization (15). Butts and colleagues further demonstrated that the fungicidal activity of toremifene against Cryptococcus neoformans is based on inhibition of calcineurin signaling via calmodulin binding (17). The findings of these two studies regarding the antifungal/antibiofilm mode of action of toremifene are in line with the well documented antifungal mechanism of action of its close analogue tamoxifen, which is based on membrane perturbation and interference with calcium homeostasis and calcineurin signaling (18)(19)(20).…”
mentioning
confidence: 99%
“…The results demonstrated that calmodulin mutants showed increased sensitivity to miconazole, terbinafine, or itraconazole compared with the sensitivities of the parent strains. Recently, another report demonstrated that the estrogen receptor antagonists tamoxifen and toremifene exerted their anticryptococcal activity alone or in combination with fluconazole and amphotericin B by directly binding to the essential EF-hand protein calmodulin, which prevented calmodulin from binding to its wellcharacterized substrate calcineurin and blocked calcineurin activation (110). This finding indicated that calmodulin antagonism contributes to the antifungal activity of this scaffold.…”
Section: Interference With Calmodulinmentioning
confidence: 99%
“…Additionally, loperamide, a diarrhoea drug, was repurposed against Salmonella enterica (Ejim et al , 2011). The breast cancer drug tamoxifen showed efficacy in a murine model of cryptococcosis (Butts et al , 2014). Chlorcyclizine, an old antihistamine, was repurposed for the treatment of infections by the hepatitis C virus (He et al , 2015).…”
Section: Drug Repurposingmentioning
confidence: 99%